Pendampingan Penggunaan Aplikasi Cinta Qur’an Pada Program Ngaji Gaul Dalam Kuliah Pengabdian Masyarakat (KPM) DI TPQ As-Syifa Dusun Kemloko, Desa Bumiayu, Kecamatan Selopampang, Kabupaten Temanggung - Alifa Noor Azzah; Wafa Nur Nadila; Wafiq Azizah; Dwi Riski Suandi; Laili Ermawati; Syahrul Ardiansyah; Madarina Rosyqoh; Lutfiah Al Kharimah; Novan Syahrurromadhon; Rahmatia Hirda Al Husna; Iyan Almas Albantani; Indra Cahyo Maulana; Muhammad Ibnu Nabil; Ahmad Robihan (STIKES Columbia Asia Medan, 2025)
This assistance aims to build a positive image of religious activities, especially learning the Qur'an, able to present a relaxed, contemporary, easy-to-remember approach, and effective in attracting interest and reducing dependence on gadgets that plunge into bad things. This assistance was carried out at TPQ As-Syifa Kemloko Hamlet, Bumiayu Village by utilizing the